(untitled) - Kumar, Nirmalya (Boston, MA., 2004)
This book challenges marketers to change their role from implementers of traditional marketing functions to strategic coordinators of organization-wide initiatives aimed at profitably delivering value to customers. Kumar outlines seven cross-functional and bottom-line oriented initiatives that can put marketing back on the CEO's agenda-and elevate its role in shaping the destiny of the firm.
Keywords: Strategic planning,Marketing